Longitudinal assessment of cognitive decline in the Amish: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Song, Yeunjoo E.; Miskimen, Kristy; Laux, Renee A.; Fuzzell, M. Denise; Fuzzell, Sarada L.; Sewell, Jane L.; Miller, Sherri D.; Adams, Larry D.; Caywood, Laura J.; Prough, Michael; Close, Jason E.; Herington, Sharlene D.; et al.
Abstract: Background: The Modified Mini‐Mental State (3MS) is a widely used measure of global cognition. The Old Order Amish are both genetically and environmentally homogeneous, with similar years of formal education across the population. Here, we investigated the longitudinal course of cognitive function as measured by the distribution of 3MS in the Mid‐Western Amish. Method: After extensive QC, the 919 subjects with both baseline 3MS and AD status were analyzed. The change from 1 st to 2 nd measurement was used as the main longitudinal trait of interest. Mean decline differences in 4 baseline age groups (<70, 70‐80, 80‐90, >=90) were assessed. The differences in the average longitudinal decline of 3MS between AD cases and controls was assessed using Kolmogorov‐Smirnov tests and ANCOVA adjusted for age at exam and sibship. Result: The overall baseline mean 3MS score was 89.52 [42, 100] at the mean age of exam 75.52 [60, 99]. The overall annual rate of decline was ‐0.3 [‐5, 5] from 1 st to 2 nd measurement (n=242) and ‐0.6 [‐2.1, 1.3] from 2 nd to 3 rd measurement (n = 23). The annual rate of decline was ‐0.96 [‐4, 1.7] in AD cases (n=18), ‐0.01 [‐5, 5] in AD controls (n=180) and ‐1.08 [‐5, 0.7] in an 'Unclear' group (n = 44). The most rapid annual decline of the 3MS was in age 80 to 90 group and the decline rate was significant (p‐value=0.004) compared to the lowest age group (<70) overall and in AD cases. In the Unclear group, the rate of decline was greatest in age 70 to 80. However, in the control group, cognition improved, with a 1.29 [‐1, 5] annual increase in age 80 to 90. The age and sibship adjusted differences in decline were significant (p‐value<2e‐10) between AD cases vs. controls as well as between Unclear vs. controls. Conclusion: We explored the changes of 3MS scores over time and demonstrated different patterns of decline by age and AD status in the Amish. Our study is the first in this homogeneous Amish population, providing a better understanding and insight into the cognitive decline examining the change in 3MS over time.